2017
DOI: 10.1016/j.repce.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to cardiac resynchronization therapy: A prospective cohort study

Abstract: Introduction: Cardiac resynchronization therapy (CRT) has modified the prognosis of chronic heart failure (HF) with left ventricular systolic dysfunction. However, 30% of patients do not have a favorable response. The big question is how to determine predictors of response. Aims: To identify baseline characteristics that might influence echocardiographic response to CRT. Methods and Results:We performed a prospective single-center hospital-based cohort study of consecutive HF patients selected to CRT (NYHA cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, decreasing cutpoint to 15, lower TAPSE values, meaning moderate and severe RV dysfunction, associated to CRT nonresponse. We concluded that TAPSE was the only parameter in multivariate analysis associated to being a CRT responder, pointing out the importance of right ventricular function for CRT response in CHF patients [55].…”
Section: Imaging Predictive Factorsmentioning
confidence: 77%
See 1 more Smart Citation
“…However, decreasing cutpoint to 15, lower TAPSE values, meaning moderate and severe RV dysfunction, associated to CRT nonresponse. We concluded that TAPSE was the only parameter in multivariate analysis associated to being a CRT responder, pointing out the importance of right ventricular function for CRT response in CHF patients [55].…”
Section: Imaging Predictive Factorsmentioning
confidence: 77%
“…Our group analyzed several variables, clinical, functional, echocardiographic and scintigraphic, as possible predictive factors for response to CRT, in the first 79 patients studied (68% male, mean age 68.1±10.2 years, 24% ischemic) [55]. At 6 months, 62% were considered as echocardiographic responders.…”
Section: Imaging Predictive Factorsmentioning
confidence: 99%